PRAKTIK RUWAT DESA SEBAGAI TRADISI MASYARAKAT PETANI: Studi Etnografi di Desa Wunut, Porong Sidoarjo - Clarissa Ayu Fitri Ramadhani; FX Sri Sadewo (Universitas Andalas, 2025)
Ruwat Desa, a Javanese agricultural ritual, persists in Wunut Village, Sidoarjo, despite losing 66% of farmland to industrial conversion (1985-2024). This pattern appears across Java's industrializing regions, where villages lost 45-65% of agricultural land, yet ritual participation declined only 15-20%. How does an agricultural ritual persist when its material foundations vanish? Existing frameworks fail: Geertzian involution explains cultural maintenance through agricultural intensification, not cultural intensification when land disappears. This study applies Bourdieu's practice theory to reveal capital substitution, communities strategically replace declining economic capital with enhanced cultural and symbolic capital. Three-year ethnographic research (2022-2024) with 10 informants demonstrates three mechanisms: funding shifted from 85% farmer contributions (pre-1990s) to 60% non-farmer sources (post-2000s); communities preserve core elements (sacred site, wayang performance) while adapting peripherals (gunungan contents, organization); generational habitus transformed from cosmological conviction to pragmatic observance to heritage valorization. Cultural sustainability operates through strategic capital restructuring rather than material continuity, advancing beyond predictions of cultural decline and offering insights for agrarian-industrial transitions across Indonesia and the Global South.